CATALYTIC ESTERIFICATION OF GUM ROSIN FROM PINE SAP - Natasya, Emerentia
Gum rosin is a derivative of pine resin with significant potential in various industries. However, the use of unmodified gum rosin presents drawbacks due to its tendency to crystallize, its susceptibility to oxidation in open air, and its reactivity with heavy metal salts in varnishes. Consequently, modification of gum rosin derivatives is necessary. This study focuses on the esterification reaction, where the acid group of gum rosin derivatives is esterified using different types of polyethylene glycol (PEG). The types of PEG used in the experiments are PEG 200, PEG 400, PEG 4000, and PEG 6000. Additionally, Zeolite 13X catalyst was added to accelerate the esterification reaction. The primary goal of this research is to investigate the esterification process of gum rosin with PEG to produce rosin esters with low acid numbers. The optimal product was obtained using PEG 200 and Zeolite 13X catalyst at a temperature of 250°C without nitrogen, yielding an acid value of 67,885 mg KOH/g and a conversion rate of 67%. The use of nitrogen did not significantly affect the acid number of the product. Impregnation of Zeolite 13X catalyst with Fe and Ni metals did not result in better conversion rates compared to regular Zeolite 13X catalyst. In general, the conversion rate increased with rising reaction temperatures. The esterification reaction using Zeolite 13X catalyst follows second-order kinetics. The reaction rate constants at 230°C, 250°C, and 270°C were found to be 0,214 g/mg KOH·h, 0,305 g/mg KOH·h, and 0,433 g/mg KOH·h, respectively. The activation energy was determined to be 39,975 kJ/mol, with an Arrhenius constant of 3022,68